Pedagogical Innovative Methods and Classroom Management in Nigeria (Faculty of Teacher Training and Education, Universitas Terbuka, 2022)
The primary goal of this research was to determine the relationship between innovative pedagogical methods and classroom management. Traditional pedagogy has been found to be out of date in recent years, especially in terms of how teachers deliver their teaching and management of the classroom. The time is right to recognize cutting-edge educational pedagogical innovative methods that are currently being implemented on a world wild scale or locally, depending on the needs of the region. A quantitative research design was adopted for the study. A sample of 761 participants was selected randomly selected from the sample public primary schools in the North-west zone, Nigeria. Pearson product-moment correlation coefficient and linear regression analysis were used to test the hypotheses. The findings revealed that computational thinking-embodied learning and context-based learning positively and significantly correlated with classroom management. Therefore, it was recommended that School managers should continue to encourage learners' computational thinking so as to help learner experience a deeper level of involvement and understanding. Also, school managers should continue to improve embodied learning in order to help teachers reach out to the mind of learners and make lessons more interesting. Furthermore, school managers should encourage context-based learning by giving learners a perfect degree of autonomy over learning activities, helping learner activate their thinking and meta-cognitive skills toward achieving effective classroom management.